BIOCHEMIC:AL COMPOSITION OF THE LAMELLIBRANCHS MERETRIX CASTA (CHEMNITZ) AND SANGUINOLARIA DIPHOS (GMELIN) - Wafar, M V Mohideen (Indian Journal of Fisheries, 2011)
The two eulamellibranch bivalves, Meretrix casta (Chemnitz) (Family: Veneridae) and Sanguinolaria diphos (Gmelin) (Family: Psammobiidae) are found in Vellar estaary, Porto Novo (Lat. 11Â°29TS[ and Long. 72Â°49’E). Meretrix casta occurs in good quantities in the estuary while Sanguinolaria diphos is found in small numbers. Horaell (1917) pointed out that the clam Meretrix casta "is probably the most important food mollusc of the Madras Presidency